Arabic Grammar in Minangkabau Surau: Philological Perspectives on Traditional Islamic Education - Akhyar Hanif; Septika Rudiamon; Muhammad Fauzinudin Faiz; Cut Afrina; Arifki Budia Warman; Elvi Rahmi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study aims to uncover the reasons why Nahwu manuscripts are found in almost every surau in Minangkabau and how Nahwu, a branch of Arabic grammar, was taught in these traditional Islamic educational institutions. This research is qualitative research employing a philological approach, which seeks to describe and reveal the phenomena surrounding surau education in Minangkabau. Based on the discovery of Nahwu manuscripts, and to explore the instructional process of Nahwu in these institutions. Primary data sources include several Nahwu manuscripts, along with the leaders of Inyik Jaho Surau, Surau Labai Sati Malalo, and the SurauSyaikh Abbas Padang Japang. Secondary data sources comprise various books, articles, and other related references. The research finds that the Nahwu manuscripts discovered in these surau represent the most authentic evidence of Islamic educational traditions in historical Minangkabau. Nahwu was not only considered essential for understanding religious texts but also regarded as an integral part of religious life. Instruction was delivered through the sorogan method, whereby teachers would recite and guide the memorization of Nahwu texts, translate them, and apply them to the study of other religious books. Nahwu material was taught progressively in three levels: elementary, intermediate, and advanced, each with its respective classical texts.